Potential of Bacteriophages as Non-Alcoholic Antiseptic Hand Sanitizer - Sunarti, Riri Novita; Ike Apriani; Septa Ardiyan Muka Rohma; Adam Ramat hidayat; Frety Abelia Azzumar; Salem Ebraiek (Faculty of Science and Technology Universitas Islam Negeri Raden Fatah Palembang, 2025)
Bacteriophages, or phages, are viruses that can infect and replicate within bacterial cells, such as Escherichia coli. Phages demonstrate a strong ability to lyse host bacteria and exhibit high survivability, making them a promising innovation for use in non-alcoholic antiseptic products, such as hand sanitizer sprays and bacteriophage gels. This study aims to evaluate the effectiveness of bacteriophage-based hand sanitizer sprays and gels in reducing E. coli growth and total microbial colonies on palms, compared to commercial alcohol-based hand sanitizers. The method used in this study is a descriptive quantitative approach using an experimental method, specifically the Hand Sanitizer Spray and Bacteriophage Gel Test as Non-Alcohol Antiseptics. The average total bacterial colonies on male palms for the control treatment, phage gel sanitizer and commercial gel hand sanitizer were 1.95 x 104 CFU/mL; 1.15 x 103 CFU/mL; 2.55 x 103 CFU/mL, respectively, while on female palms, the values were 2.35 x 104 CFU/mL; 3.05 x 103 CFU/mL; 1.65 x 103 CFU/mL. The average total bacterial colonies on male palms for control treatment, phage sanitizer spray and commercial sanitizer spray were 1.30 x 105 CFU/mL; 2.05 x 103 CFU/mL; 9, 04 x 104 CFU/mL, respectively, while on female palms, the value was 1.58 x 105 CFU/mL; 8.36 x 103 CFU/mL; 8.79 x 104 CFU/mL. The results demonstrated that both bacteriophage hand sanitizer gel and spray significantly reduce bacterial colonies on palms, with phage-based hand sanitizer showing greater efficacy than commercial alcohol-based hand sanitizer.